A Critical Review of Education Policy Provisions in Nepal Focusing on Basic Education - Bisna Acharya; Surya Sigdel (Interdisciplinary Journal of Management and Social Sciences, 2024)
This study aims to conducting a comprehensive review of education policy provisions that pertain to elementary school education. An analytical research design has been employed to thoroughly examine policies from a critical standpoint. An extensive analysis was carried out to investigate the provisions of education policy, encompassing various policies such as those outlined in the constitution, education policies, education acts, and laws. Education was provided at no cost, with students receiving complimentary textbooks, scholarships, and tuition waivers. These benefits were available to students for the duration of their entire educational journey, without any fees. The findings indicated that the education policies of offering complimentary and compulsory education in elementary and primary school were positively received. This study offers valuable insights for creating precise guidelines to efficiently implement policies. One strategy is to incorporate an educational plan that encompasses the entire policy implementation process. In conclusion, the findings of this study indicate the importance of implementing future policies that support the development of hostels, educational programs, and personalized care approaches for children who are facing academic difficulties.